The impact of reforms on the value relevance of accounting information: evidence from Iran - Khanagha, Jamal Barzegari; Ramadilli Mohd, Shamsher Mohamad; Hassan, Taufiq; Muhamad Sori, Zulkarnain (Academic Journals, 2011)
This paper examines the value relevance of accounting information in Iran for the period 1996 - 2008, before and after the codification of national accounting standard in 2001, which could describe the effect of codification of the first national accounting standards by The Iranian Association of Certified Public Accountants. The results obtained from a combination of regression and portfolio approaches, show accounting information in Iran is value relevant and value relevance of Earnings Per Share (EPS) is higher than book value of equity per share (BVP). Moreover, a comparison of the results for the periods before and after reform, based on both regression and portfolio approaches, shows a decline in value relevance of accounting information after the reform in accounting standards. It could be interpreted to mean that codification of the first national accounting standards did not improve relevancy of accounting numbers in the Tehran stock exchange.